2010
DOI: 10.1001/archdermatol.2010.322
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Bullous Pemphigoid With Cerebrovascular Disease and Dementia

Abstract: Objective: To investigate the relationship between bullous pemphigoid (BP) and neurologic disease.Design: Case-control study.Setting: Tertiary care center for immunobullous diseases and skin tumor clinics at a university hospital in Oxford, England.Participants: Ninety consecutive patients with BP and 141 controls.Main Outcome Measures: Age-adjusted prevalence of neurologic disease in patients and controls. Time interval between the diagnosis of neurologic disease and BP and type of associated neurologic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
127
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 18 publications
22
127
1
4
Order By: Relevance
“…A 95% confidence interval not containing 1.00 is statistically significant at P=.05. In addition, we performed a multivariate logistic regression analysis after adjustment for age, sex, cerebrovascular disease and dementia (which are associated with BP as previously shown by our group 15 ), and patient comorbidities for drugs that were significantly associated with BP in the univariate analysis. Because some drugs may be indicated for certain comorbidities, we adjusted for such confounding comorbidities in the multivariate model to examine whether the drugs were truly associated with BP.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…A 95% confidence interval not containing 1.00 is statistically significant at P=.05. In addition, we performed a multivariate logistic regression analysis after adjustment for age, sex, cerebrovascular disease and dementia (which are associated with BP as previously shown by our group 15 ), and patient comorbidities for drugs that were significantly associated with BP in the univariate analysis. Because some drugs may be indicated for certain comorbidities, we adjusted for such confounding comorbidities in the multivariate model to examine whether the drugs were truly associated with BP.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…13,14 Although the use of antidepressants and antiepileptics appeared to be greater in the BP group on initial univariate analysis, this finding was not significant on multivariate analysis when relevant comorbidities are taken into account (Table 2) and may reflect the known association of BP and neurological disease. 15,19 Our group has previously shown that BP patients have significantly increased rates of neurological disease, specifically dementia and cerebrovascular disease. 15 In most of these patients, BP developed after the neurological disease.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7 A relação causal entre as doenças do foro neurológico e a ocorrência de penfigoide bolhoso tem sido muito investigada nos últimos anos. [1][2][3][4][5]7 Embora a sua patogénese ainda não esteja totalmente esclarecida, acredita-se que os processos neurodegenerativos possam predispor o desenvolvimento de PB, através da ativação de mecanismos autoimunes, que produzem autoanticorpos contra antigénios presentes nas células cutâneas e do sistema nervoso central. [1][2][3][4] Estas observações são reforçadas pelo facto de ambos os tecidos (cutâneo e sistema nervoso) serem originados a partir da crista neural.…”
Section: Discussionunclassified
“…1,2 Vários estudos recentes demonstraram a associação entre a ocorrência de PB em doentes com síndromes neurológicas como esclerose múltipla, doença de Parkinson, epilepsia e doenças cerebrovasculares. [1][2][3][4][5] Os mecanismos fisiopatológicos subjacentes a este processo ainda não estão totalmente esclarecidos. A hipótese mais plausível tem como base a reatividade imunológica cruzada entre autoanticorpos das células cutâneas e do sistema nervoso central, potenciada pela perda de tolerância imunológica que está associada ao processo de envelhecimento e ao aparecimento de sín-dromes demenciais.…”
Section: Introductionunclassified